PENGARUH LATIHAN H-MOVEMENT DAN X- PATTERN MULTI SKILL TERHADAP KELINCAHAN DALAM PERMAINAN SEPAK BOLA DI SMA NEGERI 10 GOWA - Suwardi, Suwardi; Badaru, Benny; Ihsan, Andi; Sulfitriyono, Sulfitriyono (UNIVERSITAS NEGERI MAKASSSAR, 2022)
This study aims to determine whether there is an effect of H-Movement and X-Pattern Multi Skill training on agility in the soccer game of students at SMA Negeri 10 Gowa. A total of 20 students became research subjects taken randomly from a total population of 45 students. This study uses an experimental model with